(untitled) (Civil Engineering Dimension, 2024)
Expansive soils are widespread in Indonesia, particularly in Banten Province, causing extensive road damages. The study aimed to predict the soil expansivity of soil subgrade along the damaged road segments in Malingping, Cikeusik-Cibaliung, and Labuan districts. Indirect and direct expansivity predictions were employed to determine soil swelling potential. Indirect expansivity prediction was conducted based on various criteria using the Atterberg limit and grain size distribution. Direct expansivity prediction was conducted using an oedometer apparatus to measure the expansion index according to ASTM D-4829. A dynamic cone penetration test was also conducted to measure CBR values. Various indirect methods showed inconclusive results of swelling potentials, low to very high. The direct method provided more conclusive results, Expansivity Index = 100-167 and swelling values = 9%-18%, thus, categorized as expansive clay (high to very high swelling potential). CBR values were 1.49%-5% which is lower than minimum provisioned CBR (6%).